Plant-Scale Circular Economy Using Biological Reuse of Electrolyte Residues in the Amino Acid Industry - Jun-Woo Kim (Bioengineering)
The amino acid industry generates significant amounts of electrolyte residues, such as ammonium sulfate, acetic acid, and phosphoric acid, which cause challenges to sustainability. This short article investigates the feasibility of implementing a plant-scale circular economy through the recycling and biological reuse of these electrolyte residues. Scenario analyses of L-lysine (LYS) HCl, L-methionine (MET), and L-cysteine (CYS) HCl production highlight the environmental and economic benefits of the plant-scale circular economy. Despite these advances, challenges remain, including improving reuse rates for residues and reducing sodium ion content in the salt. This analysis emphasizes the need for integrated process design to enhance the circular economy, not only in amino acid production but also in other fermentation-based industries.